2021
DOI: 10.1590/fst.27720
|View full text |Cite
|
Sign up to set email alerts
|

Determination of some chemical compounds of bignay (Antidesma bunius) fruit juice

Abstract: Bignay fruits are produced from wild trees of Antidesma bunius Spreng which can be found in India, Ceylon, and South East Asia countries. Each mature tree can produce hundreds of kilograms of fruits per year, so this fruit has the potential to be used as a raw material in juice and beverage industries. In addition, recent trends in consumer demand indicates that consumers are more inclined to demand products which can provide health benefits. In order to assess the potential of bignay fruit as a raw material f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
(36 reference statements)
0
9
1
Order By: Relevance
“…It is important to note that based on the results obtained from the DPPH method, bignay fruit juice heated by ohmic heating at 90 and 110 °C provided higher antioxidant activity than that at 70 °C (p < 0.05). In fact, the antioxidant activity of ohmically heated bignay juice at 90 °C exhibited no significant difference from that of fresh bignay fruit juice in our previous study (Hardinasinta et al, 2020). This implies that higher temperature showed a positive effect on antioxidant activity.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…It is important to note that based on the results obtained from the DPPH method, bignay fruit juice heated by ohmic heating at 90 and 110 °C provided higher antioxidant activity than that at 70 °C (p < 0.05). In fact, the antioxidant activity of ohmically heated bignay juice at 90 °C exhibited no significant difference from that of fresh bignay fruit juice in our previous study (Hardinasinta et al, 2020). This implies that higher temperature showed a positive effect on antioxidant activity.…”
Section: Discussioncontrasting
confidence: 49%
“…Exotic fruits from tropical countries such as bignay (Antidesma bunius), Indian black plum or jamun (Syzygium cumini L), red mulberry (Morus rubra L.), and black mulberry (Morus nigra L.) have gained interests from researchers for their potential as sources of bioactive compounds and natural antioxidants. Studies on bignay fruits (Butkhup & Samappito, 2008;Hardinasinta et al, 2020;Jorjong et al, 2015;Lim, 2012;Ngamlerst et al, 2019), black plum (Aqil et al, 2012;Banerjee et al, 2005;Singh et al, 2018), and mulberry (Isabelle et al, 2008;Kim et al, 2010;Zhang et al, 2008) indicate that these fruits are rich in phenolic compounds such as flavonoids and athocyanins which have the potential to provide health benefits as reported by numerous authors (Aiyer et al, 2008;Basli et al, 2017;Chowtivannakul et al, 2016;Mazza, 2007;Ngamlerst et al, 2019;Stoner et al, 2007;Timmers et al, 2015;Wang & Stoner, 2008). Bignay fruit is an exotic fruit which is mostly found in Southeast Asian countries such as Thailand and Indonesia.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, no studies have examined the content of volatile compounds and essential oils in the fruit of Antidesma bunius. (Hardinasinta et al, 2020;Jorjong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity of fruit juices is the synergistic effect of different antioxidants existing in the juice [24]. Hardinasinta et al [12] reported that Mao juice has relatively high antioxidant activity, and significant correlation was found between the antioxidant capacity and some polyphenolic compounds. The antioxidant activity of Mao fruits is related to gallic acid, ferulic acid, and some anthocyanins, mainly cyanidin-3-O-glucoside [6].…”
Section: Phytochemical Contents and Antioxidant Activitymentioning
confidence: 99%
“…Seeds and marcs are abundant sources of polyphenols and proanthocyanidins [9]. While the fruit juice contains high amounts of several bioactive components such as phenolics, ascorbic acid, anthocyanins, and flavonoids [10][11][12]. Mao fruit extracts exhibited antimicrobial properties [13].…”
Section: Introductionmentioning
confidence: 99%